A INTERDISCIPLINARIDADE INTRÍNSECA NAS AÇÕES DESENVOLVIDAS NO PIBID - Tucci de Carvalho, Ana Márcia Fernandes (2019)
This research analyzes issues related to the implementation of interdisciplinary approaches in the different subprojects under development in PIBID/UEL. For this purpose, we deepen in teacher training and the concept of interdisciplinarity. Theoretically, we approach how the interdisciplinarity is presented in the official documents which rule PIBID, so the methodological choice was the documentary analysis. Empirically, we collected data from the reports of the participants during an event and we focused on the study of a project developed in the area of Mathematics, with the African Culture theme. The data analysis points out that the interdisciplinarity included in PIBID / UEL materializes from projects and/or subjects under the regency of the teacher of specific areas. We are faced with the challenge of understanding such transdisciplinary actions and expanding them to other subprojects.